Comprehensive review of innovation in piston engine and low temperature combustion technologies - Allmägi, Roland; Ilves, Risto; Olt, Jüri (Transport, 2024)
Global transport today is mainly powered by the Internal Combustion Engine (ICE) and throughout its century and a half of development it has become considerably more efficient and cleaner. Future prospects of the ICE rely on the scientific work conducted today to keep this trend of higher efficiency and cleaner emissions in new engines going. The aim of this article is to give a comprehensive review of development directions in novel piston engine designs, which seek to overcome the drawbacks of the ubiquitous 4-stroke piston engine. One of the directions of development is devoted to improving the mechanisms and the general layout of the piston engine to reduce losses within the engine. Research teams working with alternative engine work cycles like the 5- and 6-stroke engine and technologies for extracting waste heat seek to reduce thermal losses while novel layouts of valve trains and crank assemblies claim to significantly improve the mechanical and Volumetric Efficiency (VE) of piston engines. These novel ideas include camless or Variable Valve Action (VVA) and engines with Variable Compression Ratio (VCR) or opposed pistons. One alternative approach could also be to totally redesign the reciprocating mechanism by replacing the piston with some other device or mechanism. Additional scientific work is investigating Low Temperature Combustion (LTC) technologies such as Turbulent Jet Ignition (TJI) and Homogeneous Charge Compression Ignition (HCCI) and its derivatives like Premixed Charge Compression Ignition (PCCI) and Reactivity Controlled Compression Ignition (RCCI) that have shown improvements in thermal and fuel conversion efficiency while also significantly reducing harmful emissions. These combustion strategies also open the path to alternative fuels. The contemporary work in the combustion engine fields of research entail technical solutions from the past that have received a modern approach or are a completely novel idea. Nonetheless, all research teams work with the common goal to make the piston engine a highly efficient and environmentally friendly device that will continue to power our transport and industry for years to come. For this, solutions must be found to overcome the mechanical limitations of the traditional layout of the piston engine. Similarly various improvements in combustion technology are needed that implement state of the art technology to improve combustion characteristics and reduce harmful emissions.